Colleges and schools-College of Agricultural Sciences and Technology-Viticulture and Enology 105
Ag industry-Nick Canata, research technician at California State University, Fresno, prepares to enter a vine row with a specially designed over-the-vine spray canopy used to apply oleic acid to Thompson Seedless grapes in the university's project to develop a system for drying raisinson the vine. The oleic acid spray accelerates the dehydration of the grapes after the fruiting canes have been cut. A Chisholm-Ryder grape harvester removes the dried fruit from the vines. The spray canopy was developed by Bendt A. From, associate professor of agricultural industry and education at CSUF. Mounted on the side of a tractor, it is designed to recover 40 percent of the spray for recirculation and reapplication through the sytem. A spray tank, donated by the John Bean Division of FMC Corporation supplies the system.